Transcriptome analyses in infertile men reveal germ cell-specific expression and splicing patterns - Siebert-Kuss, Lara; Krenz, Henrike; Tekath, Tobias; Wöste, Marius; Persio, Sara Di; Terwort, Nicole; Wyrwoll, Margot J.; Cremers, Jann-Frederik; Wistuba, Joachim; Dugas, Martin; Kliesch, Sabine; Schlatt, Stefan; et al. (Life science alliance, 2023)
The process of spermatogenesis - when germ cells differentiate into sperm - is tightly regulated, and misregulation in gene expression is likely to be involved in the physiopathology of male infertility. The testis is one of the most transcriptionally rich tissues; nevertheless, the specific gene expression changes occurring during spermatogenesis are not fully understood. To better understand gene expression during spermatogenesis, we generated germ cell-specific whole transcriptome profiles by systematically comparing testicular transcriptomes from tissues in which spermatogenesis is arrested at successive steps of germ cell differentiation. In these comparisons, we found thousands of differentially expressed genes between successive germ cell types of infertility patients. We demonstrate our analyses’ potential to identify novel highly germ cell-specific markers (TSPY4 and LUZP4 for spermatogonia; HMGB4 for round spermatids) and identified putatively misregulated genes in male infertility (RWDD2A, CCDC183, CNNM1, SERF1B). Apart from these, we found thousands of genes showing germ cell-specific isoforms (including SOX15, SPATA4, SYCP3, MKI67). Our approach and dataset can help elucidate genetic and transcriptional causes for male infertility.
Online verfügbar November 29, 2022
Gesehen am 30.01.2023